Weather conditions and electoral outcomes in Taiwan. Issue 6 (1st November 2020) - Chen, Li-Ju
Abstract: This paper examines the electoral outcomes in legislative elections in Taiwan, using the weather characteristics on election day as the independent variable. The results show that weather matters for voter turnout. Moreover, rainfall on election day yields no marginal effects on the vote share of the two main parties, but benefits other small parties inclined to the right. This result responds to the argument that conservative parties benefit from lower turnout, and supplements the literature by showing that lower turnout caused by weather also yields different impacts on each political party.